2014
DOI: 10.1007/s00125-014-3166-3
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive quantification of the beta cell mass by SPECT with 111In-labelled exendin

Abstract: Aims/hypothesis A reliable method for in vivo quantification of pancreatic beta cell mass (BCM) could lead to further insight into the pathophysiology of diabetes. The glucagonlike peptide 1 receptor, abundantly expressed on beta cells, may be a suitable target for imaging. We investigated the potential of radiotracer imaging with the GLP-1 analogue exendin labelled with indium-111 for determination of BCM in vivo in a rodent model of beta cell loss and in patients with type 1 diabetes and healthy individuals.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
167
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 126 publications
(174 citation statements)
references
References 44 publications
6
167
0
1
Order By: Relevance
“…111 Inexendin-3 showed low accumulation in blood, heart, spleen, and liver (maximum, 0.1 percentage injected dose [%ID]/g). Uptake was observed in stomach, duodenum, and lungs (0.74 6 0.45, 0.51 6 0.32, and 10.0 6 5.28 %ID/g, respectively), which corresponds with previous observations (15). Kidney accumulation was high (31.9 6 11.5 %ID/g) and was not GLP-1R-mediated.…”
Section: Biodistributionsupporting
confidence: 89%
See 2 more Smart Citations
“…111 Inexendin-3 showed low accumulation in blood, heart, spleen, and liver (maximum, 0.1 percentage injected dose [%ID]/g). Uptake was observed in stomach, duodenum, and lungs (0.74 6 0.45, 0.51 6 0.32, and 10.0 6 5.28 %ID/g, respectively), which corresponds with previous observations (15). Kidney accumulation was high (31.9 6 11.5 %ID/g) and was not GLP-1R-mediated.…”
Section: Biodistributionsupporting
confidence: 89%
“…It has previously been demonstrated that targeting of GLP-1R with radiolabeled exendin is an elegant method for imaging b-cells, mainly in insulinoma models (14,19) and the native pancreas (15). This strategy was applied by Wu et al, who used PET after injection of exendin-4 labeled with 64 Cu or 18 F to visualize islets transplanted into the liver (9,20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In-labeled exendin] have been utilized in the field of human β-cell image studies (25)(26)(27). Likewise, BLI has been widely used with luciferase transgenic mice to evaluate β-cell mass under both normal and pathological conditions (17,28).…”
Section: F-fluoropropyl-(+)-dtbz and 111mentioning
confidence: 99%
“…However, quantification of β-cell mass in vivo is relatively difficult due to the lack of reliable and noninvasive biomarkers for cells (24). Recently, the use of in vivo imaging techniques including positron-emission tomography (PET) and single-photon emission computed tomography (SPECT) with isotope-labeled ligands [such as In-labeled exendin] have been utilized in the field of human β-cell image studies (25)(26)(27). Likewise, BLI has been widely used with luciferase transgenic mice to evaluate β-cell mass under both normal and pathological conditions (17,28).…”
mentioning
confidence: 99%